Unseen Bias: How AI Shapes Religious Narratives in Digital Spaces - Nurjaman, Hilman; Siregar, Achmed Faiz Yudha; Yasinta, Jasmine Rizky El (Journal Of Middle East and Islamic Studies, 2025)
This study explores the role of artificial intelligence (AI) in shaping religious narratives in digital spaces, particularly on social media platforms and AI chatbots. Using sentiment analysis and qualitative content analysis, this research examines religious discourse in Indonesia, focusing on the impact of AI-driven content personalization, such as 'filter bubbles' and 'echo chambers'. The findings indicate that AI algorithms reinforce religious biases, intensifying polarization and discrimination, especially between majority and minority religious groups. The study also highlights the socio-political factors influencing these dynamics, including identity politics, historical religious tensions, and conservative social norms. This research emphasizes the need for a more inclusive and ethical approach to AI in moderating religious content and fostering interfaith dialogue.